2014
DOI: 10.5194/acp-14-4679-2014
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison and evaluation of global aerosol microphysical properties among AeroCom models of a range of complexity

Abstract: Abstract. Many of the next generation of global climate models will include aerosol schemes which explicitly simulate the microphysical processes that determine the particle size distribution. These models enable aerosol optical properties and cloud condensation nuclei (CCN) concentrations to be determined by fundamental aerosol processes, which should lead to a more physically based simulation of aerosol direct and indirect radiative forcings. This study examines the global variation in particle size distribu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(116 citation statements)
references
References 158 publications
(179 reference statements)
7
109
0
Order By: Relevance
“…Only three models (IMPACT, GMI, GISS-MATRIX) exhibit both a low bias or RMS error and a high correlation, with no single obvious factor linking their aerosol treatments. AeroCom Phase II models use a wide variety of microphysics schemes (Mann et al, 2014). Meteorology and treatment of BC aging and wet scavenging also vary, and will impact the vertical profiles (Kipling et al, 2013;Bauer et al, 2013).…”
Section: Consequences For Bc Atmospheric Lifetimementioning
confidence: 99%
“…Only three models (IMPACT, GMI, GISS-MATRIX) exhibit both a low bias or RMS error and a high correlation, with no single obvious factor linking their aerosol treatments. AeroCom Phase II models use a wide variety of microphysics schemes (Mann et al, 2014). Meteorology and treatment of BC aging and wet scavenging also vary, and will impact the vertical profiles (Kipling et al, 2013;Bauer et al, 2013).…”
Section: Consequences For Bc Atmospheric Lifetimementioning
confidence: 99%
“…On the contrary, vertically resolved in-situ data of aerosol properties are urgently needed for model validation and improvement (Aquila et al, 2011;Mann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we demonstrated that polarization lidars have the potential to contribute to vertical profiling of cloud condensation nucleus (CCN) and ice-nucleating particle (INP) concentrations Ansmann, 2015, 2016). The retrieval of these higher level lidar products is driven by the fact that state-of-the-art environmental (regional) and global atmospheric models include aerosol schemes which simulate microphysical aerosol processes and life cycles of a variety of aerosol components and can be used to predict dust events and enable the simulation of CCN and INP profiles (Huneeus et al, 2011;Koffi et al, 2012Koffi et al, , 2016Mann et al, 2014;Kim et. al., 2014;Nickovic et al, 2016;Hande et al, 2016).…”
Section: Introductionmentioning
confidence: 99%